PERAN MARXIST THEORY OF LAW DALAM MENDUKUNG ILMU HUKUM TATA NEGARA - Mia Siratni (Ensiklopedia of Journal, 2023)
Abstract: This paper attempts to explain a little about law from a marxist perspective. Therefore, this paper is more appropriate to be positioned as an introductory article to open an understanding of the Marxist theory of constitutional law. They have used various approaches in discussing the nature of law, and even with these various approaches, the legal theory they produce has its own characteristics. This can be seen, among other things, in the existence of economic and political factors in their approach to law, as well as in the content of criticism of the capitalist system. The last mentioned, can even be considered as a spirit that tends to be typical in Marxist thought which always criticizes the capitalist system and its influence in human life. There are still many gaps and deficiencies that are expected to become material for further writing on the Marxist theory of law. The author's discussion in this paper has not gone so far as to explain the influence of Marxist theory of law in encouraging the emergence of schools of thought in legal science, has not gone so far as to explain the criticisms leveled against Marxist theory of law, and has not yet reached the forms of practice. marxist theory of law at the state level. At least, these 3 (three) things are expected to be the inspiration for subsequent writings on the Marxist theory of law.Keywords: Role, Marxist, Theory, Constitutional Law.